IMPLEMENTASI PRINSIP ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI ONLINE SHOP - Lisa, Hendro; Yuslizar (Lembaga Marwah Rakyat, 2024)
This study aims to analyze whether Online Shop has applied the principles of Islamic business etchis in online buying and selling transactions and how to apply the principles of Islamic business ethics in online buying and selling transactions. This research method is qualitative that uses the field of literature review. Data collection is done by collecting the source of articles in the form of journals and previous proceedings that are relevant. The results of the study stated that Online Shop had fully implemented the principles of Islamic business etchis in buying and selling, with the principle of unity, the principle of equilibrium, principle free will, the principle of responsibility and the principle benevolence